An investigation of the impact of axial force on friction stir-welded AA5086/AA6063 on microstructure and mechanical properties butt joints. (2021) - Ramamoorthi, R.; Yuvaraj, K.P.; Gokul, C.; Eashwar, S.J.; Arunkumar, N.; Abith Tamil Dheen, S.
Abstract: Friction stir welding (FSW) is a method through which frictional heating and plastic deformation normally joined the work pieces at temperatures under the melting temperature of the materials to be united. The aim of this study is to assess the impact of axial force during welding on the dissimilar joints mechanical properties of aluminum alloys (AA5086 and AA6063 aluminum alloy) formed by friction stir welding process. Friction stir welding is done using four different axial forces (Viz 5kN, 6kN, 7kN and 8kN) on the dissimilar aluminum alloys and the impact of these on the mechanical performance of samples were investigated in contexts of tensile and bending. The microstructural investigations of the welded joint specimen are also carried out. The mechanical characteristics of the joints were strongly influenced by the axial force applied during the welding process, based on experimental results.